2019
DOI: 10.14366/usg.18004
|View full text |Cite
|
Sign up to set email alerts
|

Fetal weight estimation by ultrasound: development of Indian population-based models

Abstract: OBJECTIVE:To examine body size and fat measurements of babies born in rural India and compare them with white Caucasian babies born in an industrialised country. DESIGN: Community-based observational study in rural India, and comparison with data from an earlier study in the UK, measured using similar methods. SUBJECTS: A total of 631 term babies born in six rural villages, near the city of Pune, Maharashtra, India, and 338 term babies born in the Princess Anne Hospital, Southampton, UK. MEASUREMENTS: Maternal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 24 publications
0
18
2
Order By: Relevance
“…The study concluded that the models performed better compared to other prevalent methods in an Indian context, including the Hadlock-4. 38 That study had a percentage error of approximately 6% 38 compared to a higher 9.1% in the present study. However, the sample size was lower than in the present study and the percentage error calculated was irrespective of GA.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…The study concluded that the models performed better compared to other prevalent methods in an Indian context, including the Hadlock-4. 38 That study had a percentage error of approximately 6% 38 compared to a higher 9.1% in the present study. However, the sample size was lower than in the present study and the percentage error calculated was irrespective of GA.…”
Section: Discussioncontrasting
confidence: 61%
“…The sample size used was 139 which was a smaller sample size that was used in present study. Hiwale et al, 38 proposed 2 new models for an Indian population derived from a sample size of 137 and validated with 36 patients. The study concluded that the models performed better compared to other prevalent methods in an Indian context, including the Hadlock-4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological variation and inadequate imaging have an impact on the sonographic estimation accuracy of the EFW, regardless of the applied formula. In addition, the accuracy of the sonographic estimation declines with birth weight [13,14] and is frequently overestimated in pregnancies thought to be large for gestational age (LGA) and undervalued in pregnancies thought to have fetal growth restriction (FGR) [12].…”
Section: Two-dimensional Ultrasound Estimation Of Fetal Weightmentioning
confidence: 99%
“…Therefore, the secondary objective of the study was to examine impact of a formula/model selection on the fetal weight estimation accuracy. For this purpose, two Indian population-based models, Hiwale-1 and Hiwale-2,[ 17 ] were compared with the Hadlock-4 model,[ 18 ] which is based on a population from the United States of America.…”
Section: Introductionmentioning
confidence: 99%